A COMPARISON BETWEEN ENGLISH AND SPANISH SUBJECTS’ TYPICALITY RATINGS IN PHONEME CATEGORIES: A FIRST REPORT - Mompean Gonzalez, Jose A. (International Journal of English Studies, 2001)
The purpose of the present study is to report the findings of an experimental task in which both native speakers of English and Spanish learners of English rated different phonetic realisations of the same phoneme (the English vowel / i 1) in terms of how good examples of that phoneme those realisations were (i.e. their typicality). Similarities or differences between both groups are also described. This study also investigates the possible determinants of such typicality ratings and differences between the determination of typicality in both groups. Implications of these findings are discussed in relation to the learning of segmental phonological categories by Spanish leamers of English.